Methodological Significance of the Theory of Immanent Interpretation by Emil Staiger – Ukrainian Monograph about the Most Multiple-Valued Swiss Philologist of the 20th century - Chervinska, Olha (Pitannâ lìteraturoznavstva, 2013)
Review on the Monograph by Oleg Radchenko “The Immanent Poetics of Emil Staiger: Philological and Philosophical Discourses” (Drohobych, 2012).